The costs and socio-economic benefits associated with the Natura 2000 network. (1st January 2014) - Gantioler, Sonja; Rayment, Matt; ten Brink, Patrick; McConville, Andrew; Kettunen, Marianne; Bassi, Samuela
The EU's Habitats and Birds Directives form the basis of efforts to conserve Europe's biodiversity, with the implementation of a network of protected areas – Natura 2000 – lying at their heart. Implementation of Natura 2000 involves substantial capital investment and requires resources for on-going management and monitoring activities. The network can also deliver a variety of socio-economic benefits, resulting from a range of provisioning, regulating and cultural services, each of which supports human well being. While there is still a lack of quantitative and monetary data for the socio-economic benefits associated with Natura 2000, there is evidence that the benefits to society are larger than the costs of managing and investing in the network. This paper reviews evidence of the costs and benefits of Natura 2000 and makes the proposals regarding future work that would improve understanding of these at a local, regional, national and EU level.